Moral submissiveness: social origin as a vulnerability for well-being on a warming planet - Weihgold, Vanessa (Frontiers in Psychology, 2024)
In recent years, the emotional experience of climate change has been studied extensively from fields like psychology, theology, sociology, and philosophy. It seems is crucial to analyze these results for possible vulnerability with regard to well-being. While climate justice research raises awareness ofn the current (social) situation of the participants which has been considered relativein relation to climate emotions, the research on climate emotions seems to bracket overlook the participant's former social situation -their family of origin. Former researchPrevious studies on injustice haves shown however that it is precisely the way people were educated on doing emotion work which that has a major influence significant impact on their experiences and whether they feel insense of control of in the situation. This being a major partGiven the importance of this sense of control forof mental well-being, I argue consequently that social origin is a vulnerability for well-being in the (emotional) experience of climate change, perpetuating climate injustice, based on this combination of studies from different epochs. As a resultTherefore, in the interest to protect well-being on a warming planet, it is important crucial to raise awareness on of the impact of social origin.